Representations of coastal risk (erosion and marine flooding) among inhabitants of at-risk municipalities. Issue 6 (3rd June 2017) - Michel-Guillou, Elisabeth; Meur-Ferec, Catherine
Abstract : As part of an interdisciplinary research programme on coastal risks, a combined environmental psychology–geography approach was used to study representations of coastal erosion and sea flooding among inhabitants of coastal areas. The relationship between these representations and place, or more specifically sense of place, will initially be examined, followed by individuals' preferred risk adaptation strategies. Face-to-face interviews were conducted with 894 inhabitants from five coastal municipalities in Brittany. Results show that coastal risks are not a top priority for respondents. Paying particular attention to respondents who spontaneously cited coastal rather than other risks or no risk, we show that their relationship to place differs from the other respondents, as do their preferred adaptation strategies. These results lead to a better understanding of attitudes towards coastal risks among inhabitants of at-risk areas and provide more in-depth knowledge on coastal zone vulnerability.